Chemical composition, pharmacological effects and applications Hibiscus sabdariffa L. (Malvaceae) in skin care and dermatology: A review - Ha, Ly Hong Huong; Yen, Nguyen Thi Hong; Nhut, Nguyen The; Man, Tieu Tu; Hanh, Nguyen Thi; Dat, Nguyen Thanh; Ngoc, Vo Thi Bich; Tuan, Huynh Minh; Thuy, Dang Thi Le (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
In recent years, it is estimated that 80% of world population rely on traditional herbal medicine for primary health care. The cosmetic preparations and functional foods derived from medicinal herbs are widely used in around the world and in Vietnam. The use of standardized medicinal herbs, with chemical compositions with antioxidant and skin-beautifying effects, is great research and interested. Bup Giam (Hibiscus sabdariffa L. Malvaceae) is a medicinal herb that is interested in skin care and alternative medicines. Therefore, in this paper, the authors will generalize the chemical composition from parts of the hibiscus plant along with pharmacological effects such as antioxidation, hypoglycemia, antihypertensive, and some research directions. Research on medicinal herbs of Bup Giam found the effect in skincare and dermatology such as acne treatment, wound healing, skin cancer resistance, antifungal. The review aims to the basis for in-depth studies on the effects of Bup Giam in skin beauty and dermatology to evaluate the importance of the chemical components of this medicinal herb applied in cosmetics and functional foods today.